2011
DOI: 10.4081/reumatismo.2007.215
|View full text |Cite
|
Sign up to set email alerts
|

Digital ulcers in a cohort of 333 scleroderma patients

Abstract: Digital ulcers (DU) at the hands are one of the more frequent and severe complications in systemic sclerosis. Data on their prevalence and distribution in the different subsets of disease are variable in the literature. We studied the frequency of DU in a cohort of 333 scleroderma patients followed in the last 10 years in our Unit. DU have been recorded in 133 patients (39,9%), more frequently in males, in patients with cutaneous diffuse form of disease and in patients with anti-Scl70 ANA specificity. Complica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 15 publications
3
11
0
1
Order By: Relevance
“…Males presented an higher risk to develop DU than female (odds ratio: 12.9; Table 3); this data reflect previous observations about an overall worse prognosis of the disease in males [8,9] and, in particular, the association between male gender and DU was already suggested by other Authors [21][22][23].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Males presented an higher risk to develop DU than female (odds ratio: 12.9; Table 3); this data reflect previous observations about an overall worse prognosis of the disease in males [8,9] and, in particular, the association between male gender and DU was already suggested by other Authors [21][22][23].…”
Section: Discussionsupporting
confidence: 89%
“…DU affect about 50% of the patients, recognizing a multifactorial and only partially known pathogenesis; in addition data present in literature about risk factors are often discordant [1,5,7,10,11,13,14,[16][17][18][21][22][23]. In this context, a generalization in estimating the risk to develop DU is reasonable if prevention is the goal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A univariate analysis on 333 patients showed a higher prevalence of DU in patients with SSc who were male, and had diffuse skin sclerosis and anti‐Scl70 antibodies. A multivariate analysis was not performed 5 . Thus, these studies confirmed some of the risk factors we identified by univariate analysis.…”
Section: Discussionsupporting
confidence: 67%
“…Because only 50–60% of patients with SSc experience a digital skin ulcer in their clinical history (1, 18), the advantage of this approach is questionable. On the other hand, a wait‐and‐see strategy exposes the patients to potential severe complications that require hospitalization and long‐term treatments (49, 50). In the Randomized Placebo‐Controlled Study on the Prevention of Ischemic Digital Ulcers Secondary to Systemic Sclerosis 1 (42), the patient's clinical history of multiple digital ulcers represents the most helpful predictor and indicator of preventive therapy.…”
Section: Discussionmentioning
confidence: 99%